2017
DOI: 10.5301/ijbm.5000281
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinicopathological Significance of CCAT2 in Chinese Patients with Various Tumors

Abstract: These results indicate that CCAT2 is a biomarker to predict tumor progression and a potential prognostic marker in multiple cancers. Additional well-designed clinical studies are needed to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…Compared to previous meta-analyses, our research has several advantages [ 13 15 ]. First of all, the included studies and cases extended from 11 studies with 1335 cases [ 13 ] to 20 studies and TCGA database with 13285 cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to previous meta-analyses, our research has several advantages [ 13 15 ]. First of all, the included studies and cases extended from 11 studies with 1335 cases [ 13 ] to 20 studies and TCGA database with 13285 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous meta-analyses, our research has several advantages [ 13 15 ]. First of all, the included studies and cases extended from 11 studies with 1335 cases [ 13 ] to 20 studies and TCGA database with 13285 cases. Moreover, we performed several subgroup analyses to further explore the role of CCAT2 in different types of tumors and also achieved a significant correlation between high CCAT2 expression and worse OS in survival curve studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LncRNAs are widely reported to regulate gene expression at epigenetic, transcriptional, and posttranscriptional levels [810] and aberrant expression of lncRNAs can be involved in cancer initiation, progression, and metastasis [1113]. Furthermore, increasing evidences suggested that lncRNAs could serve as potential biomarkers with high sensitivity and specificity in cancer detection and diagnosis [1417].…”
Section: Introductionmentioning
confidence: 99%